2020
DOI: 10.3390/ijms21165753
|View full text |Cite
|
Sign up to set email alerts
|

Alterations of Rice (Oryza sativa L.) DNA Methylation Patterns Associated with Gene Expression in Response to Rice Black Streaked Dwarf Virus

Abstract: Rice black-streaked dwarf virus (RBSDV) causes severe yield losses in rice (Oryza sativa L.) in China. Studies have shown that the mechanisms of DNA methylation-mediated plant defense against DNA viruses and RNA viruses are different. However, in rice its function in response to infection of RBSDV, a double-stranded RNA virus, remains unclear. In this study, high-throughput single-base resolution bisulfite sequencing (BS-Seq) was carried out to analyze the distribution pattern and characteristics of cytosine m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 53 publications
2
4
0
Order By: Relevance
“…Likewise, for all the methylation contexts, TEs showed a strong methylation level compared with genes. This result agrees with the important role of epigenetics in the TEs silencing, preventing their mobilization along the genome (Jones, 2012;Rabinowicz, 2003) and are in accordance with the global genome-wide methylation patterns reported in several rice species and genotypes (Feng et al, 2016;Garg et al, 2015;Li et al, 2012;Li et al, 2020;Stroud et al, 2013;Zheng et al, 2017). In fact, previous studies have shown that general methylation trends are conserved in phylogenetically distant plant species (Niederhuth et al, 2016;Zemach et al, 2010).…”
Section: Discussionsupporting
confidence: 91%
“…Likewise, for all the methylation contexts, TEs showed a strong methylation level compared with genes. This result agrees with the important role of epigenetics in the TEs silencing, preventing their mobilization along the genome (Jones, 2012;Rabinowicz, 2003) and are in accordance with the global genome-wide methylation patterns reported in several rice species and genotypes (Feng et al, 2016;Garg et al, 2015;Li et al, 2012;Li et al, 2020;Stroud et al, 2013;Zheng et al, 2017). In fact, previous studies have shown that general methylation trends are conserved in phylogenetically distant plant species (Niederhuth et al, 2016;Zemach et al, 2010).…”
Section: Discussionsupporting
confidence: 91%
“…Our observation on the expression level of RdDM pathway and DNA (de)methylation-related genes in root of NIL-23 under P-starvation stress confirmed the roles of epigenetic mechanism in the regulation of the stress-responsive genes, due to the introgressed Pup1 QTL, in providing P-starvation stress tolerance ( Supplementary Table S19 ). Our findings on the upregulated expression of MET1a, CMT1, CMT3, DRM1 (involved in DNA methylation), DNG702 (involved in DNA demethylation), and RDR3 (involved in RNA-directed DNA methylation) and downregulated expression of MET1b (responsible for maintaining CG methylation), CMT2 (responsible for maintaining CHG methylation), DRM2, DRM3, DNMT2 (involved in CHH-specific methylation), DML3, DNG701, DNG704 (involved in DNA demethylation), RDR2 , and RDR6 (involved in RNA-directed DNA methylation) corroborate with the findings of Moritoh et al ( 2012 ), Wang et al ( 2014c ), Yong-Villalobos et al ( 2015 ), Feng et al ( 2016 ), Lu et al ( 2016 ), and Li et al ( 2020 ). Interestingly, the methylation level of the genes coding for DNA (de)methylases and RDR polymerases varied significantly in their promoter regions, affecting their expression ( Supplementary Table S20 ).…”
Section: Discussionsupporting
confidence: 82%
“…In rice, OsAGO4 and OsAGO6 are both required for DNA methylation at most of their target loci (Duan et al, 2015 ). Rice genome methylation has been reported to be a new layer of epigenetic changes in response to RBSDV infection (Li et al, 2020 ). Zheng and colleagues have demonstrated that OsAGO2 represses OsHXK1 expression in rice spikelets through methylation of its promoter (Zheng et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%